BS EN 17020-1. Extended application of test results on durability of self-closing for fire resistance and/or smoke control doorsets and openable windows. Part 1. Durability of self-closing of hinged and pivoted steel doorsets (6th May 2021) - British Standards Institution,
No abstract available